(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Use of modern knowledge and technologies determines market development which grows with high rates. Today's business environment cause changes that affect the formation of the modern technologies, including business models, which generates changes not only the competencies, but I soft skills, including emotional capital, as a factor influencing the development of modern companies. Article investigates configuration during company growth process. Researching relevance and justification, the purpose of work is conception of factors, which positively influenced development of the entity, organization developments influencing on the productive direction. The aim of the article is to provide the competence concept and its components to identify interrelationship with knowledge and skills which is related to emotional intelligence as a part of emotional capital . And as the result, the emotional equity as element of competence, acting as the regulator, carries out a role of positive feedback within strategic management.